The complementary medicine (CAM) for the treatment of chronic pain: scientific evidence regarding the effects of healing touch massage - Marletta, Giuseppe; Canfora, Angela; Roscani, Francesco; Cernicchiaro, Lucia; Cutrera, Maria; Russo, Marianna; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2015)
Background and aim: Evidence-based medicine offers effective pathways of pharmacological treatment for chronic pain that may compromise the quality of life of patients; this is one of the main reasons why more and more people resort to traditional and complementary approaches, to try to maintain or regain their health. The effectiveness of the various forms of complementary treatments often cannot be proven objectively, which is why, given the need to find more concrete evidence of the effectiveness of complementary therapies with particular reference to the method of healing touch massage, a review of the literature was conducted in order to gather evidence of the efficacy of the specific method regarding pain and other health outcomes of patients with malignant disease to support a proposal for improvement, based on the practice of healing touch massage conducted by nurses. Method: Systematic review. Results: There are several examples (in some cases specifically regarding patients with tumors) of the positive effects of healing touch massage on pain, anxiety and fatigue, and also on biochemical parameters. Conclusions: The way to full recognition by both the institutional and the scientific community seems to promise fairly well, although it should be noted that the achievement of this goal will require further research avoiding the limitations of previous studies.